2003
DOI: 10.1097/00004770-200311000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Pain and Headache Secondary to Overfilling of a Root Canal

Abstract: A 35-yr-old woman was referred to the Istanbul University, Faculty of Dentistry, Oral Surgery Department with complaints of orbital pain and headache. Panoramic radiographs showed overfilling of a maxillary premolar, which caused a perforation in the maxillary sinus floor. The etiology, clinical manifestations, and treatment of this complication are discussed with emphasis on early surgical intervention to decrease the risk of a superimposed aspergillosis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Experimental studies and case reports have shown that eugenol‐containing endodontic sealers, calcium hydroxide, paraformaldehyde and iodoform can inflame nerves as well as cause bone necrosis and foreign‐body reactions (1,13,14). Deleterious effects depend on the site and intensity of the extrusion, the time interval in contact with the neural tissue and its chemical composition (1,8,11,14,15). The persistence of the extruded material can cause nerve necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies and case reports have shown that eugenol‐containing endodontic sealers, calcium hydroxide, paraformaldehyde and iodoform can inflame nerves as well as cause bone necrosis and foreign‐body reactions (1,13,14). Deleterious effects depend on the site and intensity of the extrusion, the time interval in contact with the neural tissue and its chemical composition (1,8,11,14,15). The persistence of the extruded material can cause nerve necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Endodontik tedavi kaynaklı zararlı etkiler, zarar gören alan, taşkınlığın miktarına, sinir dokusunun maruz kalma süresine, kimyasal bileşenlerin içeriğine bağlı olarak değişmektedir. [13][14][15][16][17] Alt çenede özellikle premolar ve molar diş köklerinin, mental foramen ve IAS ile yakın ilişkide olduğu ve yapıla-cak endodontik tedaviler açısından büyük önem taşıdığı bilinmektedir. Bürklein ve ark.…”
Section: Discussionunclassified
“…Extrusion of endodontic filling material which is an endodontic complication, is seen as a result of over-instrumentation during root canal treatment. [2,6] Over-instrumentation and extrusion of endodontic filling materials can cause maxillary sinus complications. [5,7] As a result of these complications, chronic sinusitis, chemical irritations of ciliated mucosa and/or Aspergillus infections of paranasal sinuses may develop.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, possible complications such as displacement of endodontic materials into the maxillary sinus may develop. [2] In this case report, we present a patient complaining about the pain and swelling in her right maxillary sinus area. Radiographic examination showed a dense foreign material in maxillary sinus and the patient history revealed previous endodontic theraphy and extraction of the tooth #15 because of the discomfort and pain.…”
mentioning
confidence: 99%